Induction of protective immune responses against a lethal Zika virus challenge post-vaccination with a dual serotype of recombinant vesicular stomatitis virus carrying the genetically modified Zika virus E protein gene. (29th April 2021) - Choi, Jung Ah; Wu, Kunyu; Kim, Gyoung Nyoun; Saeedian, Nasrin; Seon, Seung Han; Park, Gayoung; Jung, Dae-Im; Jeong, Hoe Won; Kim, Na Hyung; Seo, Sang Hwan; Lee, Sangkyun; Song, Manki; et al.
Abstract : The development of a vaccine to prevent Zika virus (ZIKV) infection has been one of the priorities in infectious disease research in recent years. There have been numerous attempts to develop an effective vaccine against ZIKV. It is imperative to choose the safest and the most effective ZIKV vaccine from all candidate vaccines to control this infection globally. We have employed a dual serotype of prime-boost recombinant vesicular stomatitis virus (VSV) vaccine strategy, to develop a ZIKV vaccine candidate, using a type 1 IFN-receptor knock-out ( Ifnar −/− ) mouse model for challenge studies. Prime vaccination with an attenuated recombinant VSV Indiana serotype (rVSVInd ) carrying a genetically modified ZIKV envelope (E) protein gene followed by boost vaccination with attenuated recombinant VSV New Jersey serotype (rVSVNJ ) carrying the same E gene induced robust adaptive immune responses. In particular, rVSV carrying the ZIKV E gene with the honeybee melittin signal peptide (msp) at the N terminus and VSV G protein transmembrane domain and cytoplasmic tail (Gtc) at the C terminus of the E gene induced strong protective immune responses. This vaccine regimen induced highly potent neutralizing antibodies and T cell responses in the absence of an adjuvant and protected Ifnar -/- mice from a lethal dose of the ZIKV challenge.